Assessment of wildlife mortality due to road networks (Zoological Records and Reviews, 2024)
Road networks are one of the most pervasive anthropogenic stressors on terrestrial wildlife, generating direct mortalitythrough vehicle collisions, indirect mortality through barrier effects on movement and dispersal, and sub-lethal stressresponses that reduce fitness in adjacent populations. This study provides a comprehensive assessment of wildlife roadmortality across Spain, Sweden, and Germany using systematic carcass monitoring on 2,840 km of surveyed roadtransects (2021-2023), national road casualty databases, and GPS telemetry data for six focal mammal andherpetofaunal species (n = 184 tagged individuals). A total of 48,241 vertebrate road casualties were recorded across312 taxonomic categories, yielding an estimated national mortality of 4.8-8.4 million vertebrates annually in Spain,2.1-3.6 million in Sweden, and 6.2-10.8 million in Germany. Road type and traffic volume were the strongest predictors ofcasualty rate (GLMM: beta = 0.72 and 0.64 respectively; p < 0.001 both), while proximity to woodland edge (< 200 m)doubled mammal collision risk. GPS telemetry confirmed that road-crossing attempts constituted 18.4-34.7% of mortalityevents in telemetered individuals of Capreolus capreolus and Bufo bufo. Hotspot analysis using kernel density estimationidentified 847 priority road segments (< 1% of monitored road length) accounting for 34.8% of all casualties. Cost-benefitanalysis of mitigation measures -- wildlife passages, drift fences, exclusion fencing, and speed reduction -- shows thatpassage infrastructure at hotspot locations achieves a benefit-cost ratio of 3.4-8.1 depending on species composition and traffic volume. These findings provide an evidence base for prioritising road ecology mitigation under EU GreenInfrastructure Strategy and TEN-T network management obligations.
Keywords: EU Green Infrastructure; barrier effects; Bufo bufo; Capreolus capreolus; GPS telemetry; wildlife passages; hotspot analysis; road kills; wildlife road mortality; road ecology